Experiences and coping mechanisms of young doctors following the death of a patient: a qualitative study - Snyders, Loreal Leslay (Department of Public Health and Family Medicine, 2022)
Background: The death of a patient can be a stressful event for doctors, but not many studies have been conducted in South Africa. The rationale for this study is to see whether our participants (junior doctors) would have similar experiences and coping mechanisms as described in the literature. A better understanding of these stressful experiences could guide management to better assist future doctors. This study included doctors with five years or less experience since qualification and included interns, medical officers and registrars working at a District Hospital in the Cape Metro Region i.e. Mitchell's Plain District Hospital. Aim: The aim of the study is to describe the experiences and coping mechanisms of doctors after the death of a patient and to assess the effects on their personal, emotional and family life. Methods: An exploratory or phenomenological descriptive qualitative study was conducted using semi-structured one-on-one interviews conducted by the primary investigator. Fifteen doctors employed at a District Hospital were included, each with less than five years work experience. Results: The core theme identified was that dealing with death is stressful for young doctors. The themes contributing to the stress included: Inexperience of doctors; sudden unexpected deaths of patients; poor coping mechanisms used; and lack of support structures. This had negative effects on their family and personal life. Conclusion: The study found that the stress of patients' deaths negatively affects young doctors and it is recommended that debriefing sessions be available and better coping mechanisms taught. This may prevent future anxiety disorders, depression and less burnout amongst young doctors. Future studies are needed to assess the effectiveness of debriefing sessions once implemented at Mitchell's Plain District Hospital.